Strategi Guru dalam Mengatasi Tantangan Pembelajaran Individual Anak Autis - Marina Syarasita; Lailil Aflahkul Yaum; Ahmad Zaki Emyus (JOEAI (Journal of Education and Instruction), 2026)
This study aims to describe teacher strategies in addressing the challenges of individual learning for autistic children at SLB B Branjangan Jember. This research used a qualitative approach with a case study method. The results indicate that teacher strategies for individual learning have been systematically developed through initial assessments, the development of individual learning programs (ILPs), and the application of methods based on behavioristic, TEACCH, and humanistic approaches. The main challenges faced include limited time, a lack of support staff, and tantrums in children when routines are disrupted. In conclusion, collaboration between teachers and parents proved to be a significant supporting strategy, with daily communication and parental involvement in school activities playing a role in children's learning success. These results underscore the importance of adaptive learning strategies, institutional support, and family involvement in the ongoing education of autistic children.   Keywords: Children with Autism, Individual Learning, Teacher Strategies